2023
DOI: 10.1097/mnh.0000000000000885
|View full text |Cite
|
Sign up to set email alerts
|

Uromodulin: more than a marker for chronic kidney disease progression

Abstract: Purpose of reviewUromodulin, a protein that is highly conserved across several species through evolution, functions to maintain homeostasis and prevent disease development and progression. Historically, the role of uromodulin has been thought to be limited to the kidney and genitourinary tract. This review highlights developments indicating a broader role of uromodulin in human health. Recent findingsAlthough initially discovered in the urine and found to have immunomodulatory properties, recent findings indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…Similar changes have been observed previously in patients with chronic or acute kidney diseases, likely indicating severe renal stress in trauma patients (22,28,33). Stress or damage to the kidney is further indicated by the consistent reduction of uromodulin fragments (36). Additional consistent and prominent changes include the reduction of fragments of CD99 and the polymeric immunoglobulin receptor (37).…”
Section: Kidney Failuresupporting
confidence: 78%
“…Similar changes have been observed previously in patients with chronic or acute kidney diseases, likely indicating severe renal stress in trauma patients (22,28,33). Stress or damage to the kidney is further indicated by the consistent reduction of uromodulin fragments (36). Additional consistent and prominent changes include the reduction of fragments of CD99 and the polymeric immunoglobulin receptor (37).…”
Section: Kidney Failuresupporting
confidence: 78%
“…A study conducted by Melchinger et al investigated the relationship between urine uromodulin, the most abundant protein found in urine, and kidney histological findings in both humans and mice [83]. Uromodulin is a glycoprotein that serves as an indicator of kidney tubular health and is produced in the ascending limb of the loop of Henle and early distal convoluted tubule [84]. The study demonstrated that higher urinary uromodulin levels correlated independently with lower tubulointerstitial fibrosis in patients enrolled in the Yale biopsy cohort undergoing a kidney biopsy and also in a mouse model of kidney fibrosis induced through unilateral ischemia/reperfusion injury to the left kidney.…”
Section: Biomarkers Of Kidney Fibrosismentioning
confidence: 99%
“…Although the predominant form of urinary uromodulin (uUMOD) is polymerized, new data suggest that non-polymerized forms exist and that retained EHP lacks GPI anchors ( 24 ). In addition to urine, non-aggregated forms of basolateral release also result in detectable serum uromodulin (sUMOD), albeit at significantly lower levels than urine concentrations ( 25 ).…”
Section: Overview Of the Structure And Biochemistry Of Uromodulinmentioning
confidence: 99%
“…Coronary artery calcification (CAC) typically accompanies advanced atherosclerosis development and serves as a predictor of future cardiovascular events ( 105 ). Uromodulin has been shown to be an inhibitor of calcification in blood and urine, reducing the risk of calcification ( 25 , 106 ). Inflammatory pathway activation and oxidative stress drive vascular smooth muscle calcification ( 107 109 ), which uromodulin counteracts by interfering with pro-inflammatory cytokine signaling (TNF-a and IL-1b mediated osteochondral signaling) and reducing phosphate-induced calcification in aortic smooth muscle cells ( 110 ).…”
Section: Relationship Between Uromodulin and Various Cardiovascular D...mentioning
confidence: 99%